Effects of low protein diet fortified with lysine and methionine on performance of layer hen - Mohan, Tenesa (2015)
Protein is one of the important nutrient in diet that needs to be fulfilled for the basic nutrient requirement of animals. Ideal protein diets are based on meeting animals’amino acid requirements for protein accretion and maintenance, while avoiding deficiencies and excesses. The present study was conducted to evaluate the effects of reducing dietary crude protein fortified with lysine and methionine on layer hen performance. Two experiments were conducted in this study. In the first experiment, a total of 144 Hisex Brown aged 16 weeks were randomly assigned to four dietary treatments. The birds were offered 17.5% to 16.5% crude protein supplemented with commercial amino acids (L-Lysine, DL-Methionine) till the birds are 32 weeks old. The amino acids from the different treatment groups were adjusted to similar levels. In continuation from the first experiment, the optimum level of the crude protein diet was maintained whilst the level of methionine and lysine was manipulated to the high,normal and low levels in the diets. A total of 144 Hisex Brown birds aged 19 weeks were used in this study with 9 treatments till they were of 32 weeks of age. Dietary treatments consisted of 0.77%, 0.97% and 1.77% lysine and 0.42%, 0.46% and 0.50% methionine in 17% crude protein. In the first experiment, higher (P<0.05) egg production, egg mass, Lactic Acid Bacteria microflora and Lactic Acid Bacteria to Enterobacteriacea ratio was observed in 17% CP. The 17% CP had lower (P<0.05) Feed Conversion Ratio and faecal pH compared to other treatment groups. The 17% crude protein diet with amino acid supplementation had a better egg production, increased small intenstine villus height, increased liver and spleen weight and promoted growth of beneficial Lactic Acid Bacteria microflora than birds fed with commercial diet. The second experiment concluded that 0.97% lysine and 0.50% methionine levels in the diets had a better Feed Conversion Ratio, Plasma Immunoglobulin G, Plasma Immunoglobulin M, increased Lactic Acid Bacteria microflora, increased Lactic Acid Bacteria to Enterobacteriacea ratio, reduced Enterobacteriacea count and faecal pH,. In conclusion, feeding 17% CP with 0.97% lysine and 0.50% methionine to layer hen could be optimal for maximizing production performance, small intestine absorptive capacity and immune response in layer hens.